Antifungal Activity and Phytochemical Analysis of Myrtaceae Leaf Extracts including the Induction of Defense Enzymes in Lettuce against Alternaria Leaf Spot - Suriyasit Somnuek; K. Thipmanee; Tanimnun Jaenaksorn (Horticultural Science and Technology, 2024)
To avoid the risk of harmful effects from synthetic fungicides on human and natural environments, our study aimed to evaluate the potential use of the indigenous Thai Myrtaceae plants as a harmless means for controlling the plant diseases.Four Myrtaceae extracts showed no phytotoxicity towards lettuce cultivated in hydroponic conditions, with notable plant-growth-promoting potential observed in lettuce treated with Callistemon viminalis (EECV).With regard to a direct effect, Melaleuca cajuputi (95% EEMC) showed the strongest inhibition of mycelial growth of A. brassicicola (85-100%), followed by 95% EECV (40-63%), while both extracts significantly inhibited spore germination (80-100%).A GC/MS and LC/MS analysis revealed terpenoids as the predominant compounds at approximately 55% and 37% in EEMC and EECV, respectively, with high concentrations of phytol (14%) and 1,8-cineole (14%) being particularly notable.As an inducer of an indirect effect of the plant extracts, the results from the experiment with 95% EEMC (15,000 and 50,000 ppm) as well as 50 and 95% EECV (15,000 and 50,000 ppm) applications was in good agreement, demonstrating significant reductions in disease severity in hydroponically grown lettuce ranging from 50 to 70% together with the induction of defense enzymes (specifically -1,3-glucanase, chitinase, and peroxidase) compared to those in the inoculated control and fungicide treatment groups.Furthermore, a correlation analysis revealed a negative correlation between disease severity and the three defense enzymes.Our findings underscore the considerable efficacy of the three botanical fungicides tested here (i.e., 95% EEMC as well as 95% and 50% EECV) for the management of Alternaria leaf spot in lettuce.
Keywords: Essential Oils and Antimicrobial Activity; Phytochemicals and Antioxidant Activities; Plant Pathogens and Fungal Diseases